Attitudes of consultant physicians to the Calman proposals: a questionnaire survey. North West Thames Diabetes and Endocrinology Specialist Group. - Mather, H. M. (BMJ Group, 1995)
OBJECTIVE--To determine the views of a large and representative group of consultant physicians on the Calman proposals, in which acute general medical services will change from being primarily consultant led to consultant provided. DESIGN--Postal questionnaires. SUBJECTS--All 236 consultant physicians in acute hospitals in North West and South West Thames regions. RESULTS--Replies were received from 179 (76%). One hundred and thirty seven (77%) indicated that they would not resume emergency residential duties, and 126 (71%) indicated that they would probably withdraw from general medical duties under these circumstances. One hundred and twenty six (70%) and 137 (77%) had not inserted a central venous line or temporary pacemaker, respectively, within the previous five years. Of 157 answering a question on the impact of the Calman proposals on the quality of patient services, 125 considered that it would be detrimental, and only 18 (11%) thought that it would be beneficial. CONCLUSION--Most consultant physicians are not prepared to resume emergency duties and could not do so without retraining in practical procedures. There is widespread antagonism to the Calman proposals, and most physicians consider that their impact on the quality of patient services will be detrimental.